Sosialisasi dan Pendampingan Masyarakat dalam Kegiatan Relokasi Permukiman Dampak Program PEMSEA Tahun 2022 di Desa Ketapang Kecamatan Mauk Kabupaten Tangerang - Puro, Sarjono; Nurmawati, Bernadete; Maria, Kiki; Marlin, Syamsu (LPPM Universitas Bung Karno, 2023)
Ketapang Village is located on the sea coast of Mauk District, Tangerang Regency, which has residential environmental characteristics that tend to be closely related to poverty and illegal land use. Slum settlements are caused by the inability of the poor to get proper housing, causing them to illegally occupy land along the riverbanks owned by the Tangerang District Fisheries Service. With the PEMSEA program in 2022, infrastructure development for mangrove conservation and ecotourism in Ketapang Waters is of course accompanied by regional planning, with improving the quality of slum settlements on the banks of the river leading to the beach. The arrangement of the slum settlement area is through relocation to land that is not far from the location where he lives because the legality of residential land is unclear. In an effort to overcome these obstacles, it is necessary to socialize and assist in understanding the community regarding relocation activities. The socialization method consists of two initial activities, namely data collection on project-affected residents and the process of implementing education and outreach activities through relocation assistance. The results of the outreach: the mechanism for planning and implementing relocation in Ketapang Village did not run smoothly, namely some residents affected by the project refused to relocate, so an approach was taken through socialization so that residents affected by the project were willing to sign a letter of intention to move to a new place of residence.